Reasons for non-participation and dropout in a longitudinal study of an app-based support service among adult patients in a psychiatric outpatient setting during the COVID-19 pandemic - Kaufmann, Luisa; Baldofski, Sabrina; Golsong, Konstanze; Kohls, Elisabeth; Rummel-Kluge, Christine (Frontiers in Psychiatry, 2025)
BackgroundIncreasing non-participation in research studies and high dropout rates in research on mental health apps compromise interpretability and generalizability of results. Analyzing underlying reasons holds promise for improving future recruitment methods, study design, and app features.ObjectiveThis study investigated reasons for non-participation and dropout among adult psychiatric outpatients in a study examining an app for self-reflection, daily structuring, relaxation, mindfulness, and psychoeducation in Germany during COVID-19 pandemic, as well as potential differences between dropouts and completers.MethodsDescriptive statistics on reasons for non-participation using an anonymous questionnaire and for dropout based on semi-structured telephone interviews were performed. Differences between dropouts and completers in sociodemographic, clinical, app-related, and daily mood data were analyzed.ResultsOf N = 88 persons approached for potential study participation, n = 57 (64.8%) participated in the app study, while n = 31 (35.2%) declined. Of n = 31 non-participants, n = 29 (93.5%) indicated specific reasons. On average, M = 1.72 (SD = 1.03) reasons were provided per non-participant, with no motivation for regular app use (n = 7, 24.1%), no interest in using an app for the presented content (n = 6, 20.7%), and no time for app use (n = 6, 20.7%) being the most common. Of n = 57 study participants, n = 40 (70.2%) were completers and n = 17 (29.8%) were dropouts. On average, M = 2.82 (SD = 1.29) dropout reasons were provided per dropout, with too severe health complaints (n = 6, 35.3%), not individually suitable contents (n = 5, 29.4%), and lack of incentives to use the app (n = 5, 29.4%) being the most frequent. Dropouts and completers did not differ significantly in sociodemographic, clinical, and app-related variables (all p > .05). Dropouts reported their mood significantly less often than completers during the first five and seven days of the intervention period (all p < .001).ConclusionsThis study provides exclusive insights into non-participation and dropout in an app study among adults with mental disorders. It identified personal motivation, app-related aspects, no interest in app-based offers, and personal health complaints as common reasons. Suggestions for improving future studies include focusing on incentives, app questionnaires, app installation, user needs analysis, and symptom severity. Early app engagement and adherence measurements (for example number of daily mood reports) may help identify potential dropouts earlier in future studies.Clinical Trial Registrationhttps://drks.de/search/de/trial/DRKS00027536, identifier DRKS00027536.